Urban Form Relationships with Walk Trip Frequency and Distance among Youth - Frank, Lawrence; Kerr, Jacqueline; Chapman, Jim; Sallis, James (American journal of health promotion, 2007)
Purpose. To assess the relationship among objectively measured urban form variables, age, and walking in youth. Design. Cross-sectional analyses of travel diary data mapped against urban form characteristics within a 1-km buffer of participant's place of residence. Setting. Youth in the Atlanta, Georgia region with selection stratified by income, household size, and residential density. Subjects. A total of 3161 5- to 20-year-olds who completed 2-day travel diaries. Diaries of those under 15 years were completed by a parent or legal guardian. Measures. Walking distances were calculated from a 2-day travel diary. Residential density, intersection density, land use mix, and commercial and recreation space were assessed within a 1-km network distance around residences. Analysis. Logistic regression analyses were performed for each urban form variable by age groups controlling for the demographic variables. All variables were then entered simultaneously into an analysis of the whole sample. Results. All five urban form variables tested were related to walking. Recreation space was the only variables associated with walking across the four different age groups. All the urban form variables were related to walking in the 12 to 15 years age cohort. For this group, the odds of walking were 3.7 times greater for those in highest- versus lowest-density tertile and 2.6 times greater for those with at least one commercial and 2.5 times greater for those with at least one recreational destination within 1 km from home. In the analysis of the full sample, number of cars, recreation space, and residential density were most strongly related to walking. Conclusions. Access to recreation or open space was the most important urban form variable related to walking for all age groups. Children aged 12 to 15 years old may be particularly influenced by urban form.